Pemeriksaan Kesehatan dan Peningkatan Pengetahuan Deteksi Dini Kanker Payudara pada Wanita Usia Subur Pekerja Kantor: Health Checks and Increased Knowledge of Early Detection of Breast Cancer in Women of Childbearing Age, Office Workers - Bestari, Astuti Dyah; Sari, Puspa; Martini, Neneng; Sudjatmiko, Budi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Women's reproductive health is a healthy state both physically, mentally, and socially. One of the reproductive health problems experienced by many women in Indonesia is breast cancer. Breast cancer is a cause of death for women with a relatively high incidence rate in Indonesia when compared to other cancer cases. As many as 70% of breast cancer cases are only detected when they have reached an advanced stage, making treatment difficult. This community service activity aims to provide education regarding early detection efforts through breast self-examination (SADARI) and health checks which are risk factors for breast cancer. This activity uses the service learning (SL) method which is integrated into a research program regarding the analysis of reproductive health problems for women of childbearing age (WUS) in the workplace. This activity was carried out at the Institut Teknologi Bandung (ITB) Jatinangor campus, which was attended by 5 female education staff. The results of the health examination showed that all participants had a normal body mass index (BMI) ranging from 21.2 to 24.4. The results of the vital signs examination showed that 1 participant had hypertension, 1 person had hypotension and 3 others were within normal limits. All participants can practice the awareness steps properly and correctly. Based on participants' suggestions and input, it is necessary to carry out regular reproductive health education activities with various topics so that women's reproductive health can be monitored well, especially for working women who spend most of their time at work.